Letter from Carl D. Duncan to Patricia Whiting, March, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan notes a breakfast the he and Whiting shared and he describes a presentation that he attended. He also provides parts of his schedule and travel plans for both himself and Whiting.